Philosophy of economics : a contemporary introduction - Reiss, Julian (New York, N.Y. ; London : Routledge, Routledge, 2013)
This is a textbook on the philosophy of economics. It introduces the epistemological, metaphysical, and ethical problems that arise in economics, and presents detailed discussions of the solutions that have been offered. Philosophy of Economics: A Contemporary Introduction is the first systematic textbook in the philosophy of economics. It introduces the epistemological, metaphysical and ethical problems that arise in economics, and presents detailed discussions of the solutions that have been offered. Throughout, philosophical issues are illustrated by and analysed in the context of concrete cases drawn from contemporary economics, the history of economic ideas, and actual economic events. This demonstrates the relevance of philosophy of economics both for the science of economics and for the economy. This text will provide an excellent introduction to the philosophy of economics for students and interested general readers alike.
Chapter 1. The Why, What, and How of Philosophy of Economics Part 1: Interpreting Economic Theory Chapter 2: Explaining Economic Phenomena Part 1-A: Rationality Chapter 3: Rational Choice Theory Chapter 4: Game Theory Part 1-B: Causality Chapter 5: Causation and Causal Tendencies Chapter 6: Mechanisms Part 1-C: Models Chapter 7: Models, Idealisation, Explanation Part 2: Methodology Chapter 8: Measurement Chapter 9: Econometrics Chapter 10: Experiments Chapter 11: Evidence-Based Policy Part 3: Ethics Chapter 12: Welfare and Well-Being Chapter 13: Markets and Morals Chapter 14: Inequality and Distributive Justice Chapter 15: Behavioral Economics and Nudge Bibliography
Includes bibliographical references (pages 301-321) and index.
CBA
Keywords: Economics -- Philosophy